The Effect of Soybean and Meloon Juice on Increasing Breast Milk Production in Mothers - Hasibuan, Darma Afni; Sari Dewi, Sri Sartika; Donna, Yunita Bella (International Journal of Public Health Excellence (IJPHE), 2022)
Soybean (Glycine Max) juice has many nutritional benefit beside full nutrient, its potension can be used to stimulate hormone of oxytocin and prolactin that are benefit for increasing production of mother’s milk. The information about an exclusive mother’s milk is just 45.95% babies get the intake and it is lower from the target in which the national data in the year 2018 show 68.74% babies have well mother’s milk intake. This research is taken to know the effect of giving soybean and melon juices toward the improvement mother’s milk production on the breastfeeding mothers. The research method is quocy experimental with sample about 20 people. Technique for sampling is purposive sampling. The result shows that there is an effect of giving soybean and melon juices with p- value = .000 with improvement of mother’s milk production. The conclusion, there is an effect for improving mother’s milk production by giving soybean and melon juices. Therefore, it is expected for the breastfeeding mothers should apply this knowledge in order it is one optional way to improve the production of mother’s milk on the breastfeeding mothers.